LITHIUM ISOTOPE FRACTIONATION IN THE SOUTHERN CASCADIA SUBDUCTION ZONE - Magna T.; Wiechert U.; Grove T.L.; Halliday A.N. (My University, 2006)
We present lithium (Li) abundances and isotope compositions for a suite of anhydrous olivine tholeiites (HAOTs) and hydrous basalt-andesitic (BA) lavas from the Mt. Shasta and Medicine Lake regions, California. The values of δ7Li vary from + 0.9‰ to + 6.4‰ and correlate inversely with distance from the trench. These data are consistent with continuous isotope fractionation of Li during dehydration of the subducted oceanic lithosphere, an interpretation corroborated by uniformly high pre-eruptive H2O contents in basaltic andesites accompanied by high Li, Rb, Sr, Ba and Pb abundances. The subduction-derived component that was added to these hydrous magmas is shown to be very similar beneath both Mt. Shasta and Medicine Lake volcanoes despite characteristically distinct Li isotope compositions in the magmas themselves. More evolved andesites and dacites from Mt. Shasta have δ7Li from + 2.8 to + 6.9‰ which is identical with the range obtained for HAOTs and BA lavas from Mt. Shasta. Therefore, Li isotopes do not provide evidence for any other crustal component admixed to Mt. Shasta andesites or dacites during magmatic differentiation and magma mixing in the crust. © 2006 Elsevier B.V. All rights reserved.
Keywords: FLUIDS; ISOTOPE FRACTIONATION; LITHIUM ISOTOPES; MANTLE WEDGE; MT. SHASTA REGION; SUBDUCTION ZONE